2015
DOI: 10.1038/srep08636
|View full text |Cite
|
Sign up to set email alerts
|

Functionalised MnVI-nanoparticles: an advanced high-valent magnetic catalyst

Abstract: We discover MnVI-nanoparticles (NPs) bearing functional groups, high oxidation state, strong electron affinity, unique redox and paramagnetic nature, which opens up a new avenue to catalysis, magnetism and material application. However, its synthesis is challenging and remains unexplored because of associated serious difficulties. A simple benign synthetic strategy is devised to fabricate the high-valent NPs using mild reducing agent bromide, which transformed MnVII to valuable MnVI-species. The EELS-imaging o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…STEM–EELS analysis is a powerful tool for estimating the metal distribution in heterostructured materials and for determining the redox properties at nanointerface sites. , The STEM–EELS elemental mapping images of Co–Mn/CeO 2 are shown in Figure . It is noticed that the CeO 2 particles are agglomerated, and the Co and Mn species can be observed on the surface of CeO 2 nanocubes.…”
Section: Resultsmentioning
confidence: 99%
“…STEM–EELS analysis is a powerful tool for estimating the metal distribution in heterostructured materials and for determining the redox properties at nanointerface sites. , The STEM–EELS elemental mapping images of Co–Mn/CeO 2 are shown in Figure . It is noticed that the CeO 2 particles are agglomerated, and the Co and Mn species can be observed on the surface of CeO 2 nanocubes.…”
Section: Resultsmentioning
confidence: 99%
“…Maiti et al reported the Mn(VI) nanoparticle (MnNP)catalyzed synthesis of avones (323a) from substituted aldehydes (21k) and substituted acetylenes (48e) in THF under reux using sodium as a stoichiometric oxidant and triethylamine (Et 3 N) as the base in moderate to good yields (Scheme 216). 391 The required MnNPs were synthesized using KMnO 4 and characterized via HR-TEM, TEM, STEM-EELS, XPS, and EPR spectroscopy. The MnNPs actively participate in the catalytic cycle in the oxidative C-C coupled annulation process.…”
Section: Other Mnp-catalyzed Synthesis Of Heterocyclesmentioning
confidence: 99%
“…described the close relationship of magnetic properties to adsorption phenomena, whereas adsorption of several strongly paramagnetic compound is found to be more prominent due to the strong tendency in forming electron pairing arising from the unpaired electrons spin (Selwood P., 1946). Therefore, magnetic materials in general, indicated by magnetic moment, are good adsorbent and suitable to be used as catalyst, just like the one applied by Khamarui, et al (Khamarui S. et al, 2015). Another advantage of having magnetic nano metal-oxides particles is their synergistic to be implemented in the electromagneticsolvent heating.…”
Section: Iron-based Nanocatalystsmentioning
confidence: 99%